The identity of Anemone discoideogyna and A. robustostylosa (Ranunculaceae), described respectively from Sichuan and Guangxi, China - Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2025)
Based on examination of herbarium specimens (including type material) and observations of living plants in the wild, we demonstrate that Anemone discoideogyna and A. robustostylosa (Ranunculaceae), described respectively from Sichuan and Guangxi, China, are not essentially different from A. hupehensis (sometimes treated as Eriocapitella hupehensis) in any characters, a species widely distributed in the country (Chongqing, Gansu, Guangxi, Guizhou, Henan, Hubei, Hunan, Jiangxi, Shaanxi, Sichuan, Taiwan, Yunnan, Zhejiang). We therefore place both A. discoideogyna and A. robustostylosa in synonymy with A. hupehensis herein. As the independent generic status of Eriocapitella was not supported by molecular studies, E. hupehensis is also synonymized.